Ganoderma lucidum Polysaccharide Peptide (GLPP) for the Cancer Treatment - Imam Rasjidi; Christine Susanto (Universitas Padjadjaran, 2015)
Ganoderma lucidum mushroom (also known as Ling Zhi in China, Mannetake /Reishi in Japan) has been widely used for thousands of years to prevent and treat various diseases, such as heart disease, diabetes mellitus, viral infection, and cancer. Polysaccharides from Ganoderma lucidum has been extensively investigated for free radical scavenging activity. Both in vivo and in vitro studies suggest that G. lucidum have anti-tumor effects, which mediated by its immunomodulatory, anti-angiogenesis, and cytotoxiceffects. Ganoderma lucidum polysaccharide peptide (GLPP) which extracted from Ganoderma lucidum mycelium tissue culture, give the best quality of β-D-Glucans bioactive compounds. These biologically active glucans interact with receptors on the surface of immune cells such as macrophage and natural killer cell (NK cell) to induce immunomodulatory and tumoricidal effects. However, many studies still need to answer those mechanisms.Key words: Anti-tumor effects, β-Glucan, Ganoderma lucidum, GLPP, immunomodulatory activityGanoderma lucidum Polysaccharide Peptide (GLPP)untuk Terapi KankerJamur Ganoderma lucidum (dikenal juga dengan nama Ling Zhi di China, atau disebut sebagai Mannetake/Reishi di Jepang) telah dimanfaatkan secara luas selama ribuan tahun untuk mencegah dan mengobati beragam penyakit, seperti penyakit jantung, diabetes melitus, infeksi virus, bahkan kanker. Polisakarida dari Ganoderma lucidum telah banyak diteliti untuk aktivitas radikal bebasnya. Baik studi in vivo maupun in vitro menyatakan G. lucidum memiliki efek anti tumor, yang dimediasi oleh aktivitas imunomodulator, anti-angiogenesi, dan sitotoksik. Ganoderma lucidum polysaccharide peptide (GLPP) yang diekstrak dari kultur jaringan miselium Ganoderma lucidum memberikan kualitas terbaik dari senyawa bioaktif β-D-glucans. Senyawa bioaktif glukans ini yang berinteraksi dengan reseptor di permukaan sel-sel imun, seperti makrofag dan NK cell yang dipercaya memberikan efek imunomodulator dan tumorisidal. Meskipun masih diperlukan banyak studi lanjutan untuk menjawab mekanisme dari GLPP.Kata kunci: Anti-tumor, β-Glucan, GLPP, Ganoderma lucidum, imunomodulator